Biofortification: A responsible research and innovation strategy for the G20 - Srinivas, Krishna Ravi; Anand, P. K.; Babu, Suresh Chandra (T20 India, 2023)
Poor nutritional quality and micronutrient deficiency are major barriers to achieving goal 2 of the Sustainable Development Goals (ensuring food security and nutrition for better health), especially in developing countries, including the least developed countries. Biofortification has been widely adopted as a relevant solution with potential for expansion and diversification. New technological options such as crop genome editing and nanotechnology offer the scope to make biofortification more effective. However, biofortification cannot be a stagnant solution that can be considered a panacea. This policy brief recommends evaluating biofortification as a solution and suggests a responsible research and innovation approach to improve it continually. The brief further proposes that the G20 commits to international initiatives that consider the needs and consumer preferences in biofortification, while also localising it.